Geochemical distribution of elements in the environmental media from the surroundings of open pit areas - Bavec, Špela; Cerar, Sonja; Gaberšek, Martin; Pogačnik, Željko (Geologija, 2024)
The results of geochemical investigations - carried out within the framework of the European project LIFE IP RESTART - in the degraded areas of the Kopriva (deposit of natural stone-limestone) and Lipovški vrh (deposit of limestone for industrial purposes) open pits are presented. There test sites of the installation of secondary raw materials (a mixture of recycled materials and mineral raw materials) with the aim of revitalizing degraded surfaces are planned. The main goal of this study is to define the baseline geochemical distribution of elements in environmental materials (rocks, soil, stream sediment and surface water) for the purpose of monitoring the potential environmental impacts of installed secondary raw materials. In rocks Ca content predominates due to the geological setting (predominantly limestone) of the studied areas. According to the legislative guidelines for soil, exceedances have been found for Pb in one sample (origin can be natural or anthropogenic) and Ni in two samples (presumably natural origin) from the area of Kopriva. In the area of Lipovški vrh in the stream Suhi Potok, higher contents of Mg, Na, Sr, Ca, Mn and S occur in the downstream sediment compared to upstream sediment. It is assumed higher contents occur due to anthropogenic contribution of carbonate material along the stream (washing of materials from nearby open pit and road). In the surface water of Suhi Potok, higher concentrations of S, Sr, B, U and Zn were determined. However, the concentrations did not exceed the legislative guidelines.